The Dir meta-volcanic sequence: Calcalkaline magmatism in the Kohiatan Arc terrane, northern Pakistan - Shah, Mohammad Tahir; Shervais, Jhon W.; Ikramuddin, Mohammad (Journal of Himalayan Earth Sciences, 1994)
A variably deformed and metamorphosed NE-SW trending belt of Dir metavolcanic sequence is exposed within the north-western portion of the Kohistan arc terrane. The sequence is mainly composed of massive and sheared volcanics and pyroclastic breccia. The petrochemical indices suggest that they are dominantly basaltic-andesite and andesite with subordinate basalt, dacite and rhyolite in composition. Whole rock major element compositions define a calc-alkaline trend: CaO, FeO, MgO, TiO2, A12O3, V, Cr, Ni, and Sc all decrease with increasing silica, whereas alkalis, Rb, Ba, and Y increase. Mafic to intermediate volcanic rocks show calc-alkaline affinities on petrotectonic diagrams. Chondrite-normalized REE Patterns are LREE-enriched. Dacites and rhyolites have the lowest La/Lu ratios and highest Eu/Eu* ratios, reflecting the dominant role of plagioclase fractionation in their formation. MORB-normalized spider diagrams show progressive enrichment of the low-field strength incompatible elements (Cc, La, Ba, Rb, K) and a distinct negative Nb anomaly; patterns typical of subduction related magmas. It is suggested that the high-Mg basalt of the Dir area is primitive in nature and could be the representative of the primary magnesian liquid formed by the partial melting of mantle wedge at the base of the Kohistan arc terrane. This liquid may have fractionated the other members of the sequence especially low magnesia basalt and basaltic-andesite.